Alternatives: Theorizing colonialism and Indigenous liberation: contemporary Indigenous scholarship from lands claimed by Canada. Issue 3 (1st September 2016) - Coburn, Elaine
Abstract: This essay makes the case for historical materialist scholars in universities across lands claimed by Canada to have serious engagement with Indigenous scholarship. Diverse Indigenous scholars theorize material dispossession by the Canadian state, by capital, and by non-Indigenous peoples; deconstruct dehumanizing ideologies in popular Canadian media and academic writing; and describe and analyze Indigenous resilience (survival), resistance (decolonization), and resurgence (existential self-determination). The conclusions suggest potential new collaborations across historical materialist and Indigenous scholarship in the Canadian academy.